2015
DOI: 10.1186/s13047-015-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences of foot characteristics in older Japanese adults using a 3D foot scanner

Abstract: BackgroundKnowledge of gender differences in foot shape assists shoe manufactures with designing appropriate shoes for men and women. Although gender differences in foot shapes are relatively known among young men and women, less is known about how the older men and women’s feet differ in shape. A recent development in foot shape assessment is the use of 3D foot scanners. To our knowledge this technology has yet to be used to examine gender differences in foot shape of Japanese older adults.MethodsThis cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 32 publications
3
54
0
1
Order By: Relevance
“…People with knee OA are known to possess a more pronate foot type, using foot posture index, arch index, and rear foot angles . Indeed, navicular height/foot length in this study is much lower than in healthy elderly, and we found higher prevalence rates of flat feet (49.5%) in one or both limbs in patients with knee OA. It is unknown whether the condition of flat feet causes knee pain.…”
Section: Discussionmentioning
confidence: 43%
“…People with knee OA are known to possess a more pronate foot type, using foot posture index, arch index, and rear foot angles . Indeed, navicular height/foot length in this study is much lower than in healthy elderly, and we found higher prevalence rates of flat feet (49.5%) in one or both limbs in patients with knee OA. It is unknown whether the condition of flat feet causes knee pain.…”
Section: Discussionmentioning
confidence: 43%
“…We have not recorded the foot morphology of the participant in this study. Mahshid et al reported that Japanese women had narrower feet in the heel and forefoot, and their instep, rst and fth toes and navicular height were also lower than men's [27]. Zhao et al demonstrated that Japanese men generally had longer, larger and higher arched feet than women [28].…”
Section: Discussionmentioning
confidence: 99%
“…We have applied ADA separately for men and women, since previous studies have shown gender foot shape differences [5,7]. Furthermore, footwear designers usually propose different designs for women and men.…”
Section: Resultsmentioning
confidence: 99%
“…It is not only important from the shoe manufacturing point of view, since an improper fit prevents shoe purchase, but also because poorly fitting footwear can cause foot pain and deformity [1], especially in women. Therefore, numerous studies have been carried out on foot shapes [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation